The Influence of the United Nations Guiding Principles on Business and Human Rights (UNGP) on Multinational Corporations (MNC) Employment Practices in Emerging Markets: Case Study of Indonesia - Felica Sharon; Kevin Reinaldi; Patricia (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Multinational Corporations (MNCs) have been crucial to global economic growth since the rise of globalization, contributing to one-third of the global economy, two-thirds of international trade, and employing over 40 million workers worldwide. Some MNCs are wealthier than many sovereign states, reflecting their immense influence. However, this power is often unchecked by global regulations, with MNCs operating under local laws, which in developing countries can be weak or poorly enforced. This regulatory gap allows for the exploitation of resources, labor, and the environment. In Indonesia, MNCs such as Freeport-McMoRan, Unilever, and Phillip Morris International have been linked to labor rights abuses, including unsafe working conditions and low wages. To address these issues, the United Nations introduced the UN Guiding Principles on Business and Human Rights (UNGP) in 2011, built on three pillars: protect, respect, and remedy. Although non-binding, the UNGP has become a global standard for ethical business practices. This study examines how MNCs in Indonesia adapt their policies to align with international human rights standards, with emphasis in its employment practices, using a descriptive-qualitative method based on literature studies. The findings reveal that MNC compliance with the UNGP varies depending on the industry, local governance, and corporate governance. Challenges such as weak regulatory enforcement and socio-economic disparities hinder the full application of the UNGP in Indonesia. The study emphasizes the need for stronger government oversight and corporate accountability to ensure fair and sustainable employment practices in emerging markets like Indonesia.